Nutrition for physical fitness and athletic performance for adults
It is the position of The American Dietetic Association and The Canadian Dietetic Association to support access to accurate and appropriate information that explains the interrelationships between exercise and nutrition, reinforces the important role of nutrition, and encourages appropriate food choices to achieve optimal physical fitness and athletic performance. North Americans have become more physically active and participate in exercise programs for health benefits and recreation. People of all ages are physically active and their level of participation varies from recreational walking to competitive sports. Proper nutrition plays an important role in maximizing everyone's ability to maintain higher levels of physical activity, regardless of age and type of activity. Hard physical training has the potential to affect health negatively by increasing the risk of dehydration and increasing nutrient needs. Therefore, it is important to clarify and quantify the specific stressors that varying levels of physical activity introduce on people of different ages, genders, and health status. These stressors, as they apply to different populations, should be a major thrust in the development of nutrition education materials. Physical activity is beneficial to everyone's health, regardless of their initial level of fitness. The most significant benefits are experienced by those at the lowest fitness level who become more active, even in very-low-level activities (2). For those who wish to begin a new exercise program, it is important to consider the guidelines for beginning and maintaining exercise programs provided by the American College of Sports Medicine (3,4). Although the benefits of diet and exercise are well established,individuals with certain clinical conditions, including diabetes, cardiovascular disease, and metabolic disorders, should consult a physician before initiating any exercise program. Although a moderate exercise program (40% to 60% VO2max) can be started by most individuals of any age, men over age 40 and women over age 50 who plan to begin a vigorous exercise program (> 60% VO2max) should first consult a physician (5).